Pneumosinus dilatans: A rare case report and review of literature - Priya Ramani; V R Nithya; J SreeDevi; A C Vinod Kumar (Wolters Kluwer Medknow Publications, 2021)
Pneumosinus dilatans is a rare entity that is documented only by a few reports. It is an abnormal expansion of the aerated frontal sinus, with sinus walls of normal thickness. The bone expansion is focal. A case was reported in our dental college; a 28-year-old male complaining of prominence on his forehead and it has an unknown cause and no functional problems. Computed tomography shows extension pneumatization and expansion of frontal sinus, which is extended from one side of the skull to the other side. It is benign and found to be asymptomatic. No evidence of pathological changes and no bone destruction seen. We discuss this case of etiology, clinical features, and radiological features.